Lindes entre la ficción y el documental: la puesta en escena a favor del realismo - Fernández Largo, Vanessa Talía (2019)
In this document, the different areas of creation in cinema are analyzed, dealing with the concepts and perceptions of two cinematographic genres, documentary and fiction. The purpose of this analysis is the use of both codes to create a short film that can be called hybrid, as in the case of the product obtained of this research.